A horizon scan of global conservation issues for 2014 - Sutherland, William J.; Aveling, Rosalind; Brooks, Thomas M.; Clout, Mick; Dicks, Lynn V.; Fellman, Liz; Fleishman, Erica; Gibbons, David W.; Keim, Brandon; Lickorish, Fiona A.; Monk, Kathryn A.; Mortimer, Diana; et al. (Elsevier Science B.V., Amsterdam., 2014)
This paper presents the output of our fifth annual horizon-scanning exercise, which aims to identify topics that increasingly may affect conservation of biological diversity, but have yet to be widely considered. A team of professional horizon scanners, researchers, practitioners, and a journalist identified 15 topics which were identified via an iterative, Delphi-like process. The 15 topics include a carbon market induced financial crash, rapid geographic expansion of macroalgal cultivation, genetic control of invasive species, probiotic therapy for amphibians, and an emerging snake fungal disease.
Keywords: climate change; diseases; future; horizon scan; priority setting